Internet Gaming Disorder: An Interplay of Cognitive Psychopathology - Filzah Kakul; Sarah Javed (Wolters Kluwer Medknow Publications, 2023)
Introduction: Internet addiction is currently considered a worldwide problem, with a possible impact on mental health. Young adults are recognized to be at high risk of developing Internet gaming disorder (IGD). According to a recent clinical model, young adults with IGD may endorse a distinct set of maladaptive beliefs that underlie persistent and excessive engagement in Internet gaming activities. The objective of this study was to examine the incidence of problematic gaming beliefs and psychological distress in a sample of "Indian Young Adults" with and without IGD. Methods: The research is descriptive in nature, conducted during the month of April 2022-May 2022 on a sample of 306 young adults (185 males and 121 females) recruited from multiple universities. A Google form survey that included validated measures of IGDs, Internet gaming cognition, and psychological distress were distributed on various online platforms for collecting the data. Results: According to the findings, young adults with IGD report significantly higher maladaptive gaming beliefs (t = 16.199, P < 0.001) and psychological distress (depression - t = 12.11. P = < 0.001 and anxiety/stress - t = 10.95, P = < 0.001) than young adults without IGD. The size of observed effects was large for cognition (Cohen's d = 2.14), depression (Cohen's d = 2.14), and anxiety/stress (Cohen's d = 1.96). The sample also reported strong correlation between IGD symptoms and gaming cognitions (P = <0.001). Further hierarchical regression analysis revealed depression variables as a significant predictors in the final model (β = 0.212, P = 0.002, confidence interval [CI] = 0.219-0.944) and overvaluation (β = 0.196, P = 0.020, CI = 0.048-0.545), maladaptive rules (β = 0.334, P = 0.003, CI = 0.117-0.551), and gaming social acceptance (β = 0.272, P = 0.001, CI = 0.190-0.693) as the three strongest cognition predictors of IGD symptoms. Conclusion: These findings indicate that young adults with IGD have distinct problematic thoughts about gaming and highlight the importance of addressing these cognitions in therapeutic interventions for the disorder.